National approaches to monitoring population salt intake: a trade-off between accuracy and practicality? - Corinna Hawkes; Jacqui Webster (PLoS ONE, 2012)
AIMS: There is strong evidence that diets high in salt are bad for health and that salt reduction strategies are cost effective. However, whilst it is clear that most people are eating too much salt, obtaining an accurate assessment of population salt intake is not straightforward, particularly in resource poor settings. The objective of this study is to identify what approaches governments are taking to monitoring salt intake, with the ultimate goal of identifying what actions are needed to address challenges to monitoring salt intake, especially in low and middle-income countries. METHODS AND RESULTS: A written survey was issued to governments to establish the details of their monitoring methods. Of the 30 countries that reported conducting formal government salt monitoring activities, 73% were high income countries. Less than half of the 30 countries, used the most accurate assessment of salt through 24 hour urine, and only two of these were developing countries. The remainder mainly relied on estimates through dietary surveys. CONCLUSIONS: The study identified a strong need to establish more practical ways of assessing salt intake as well as technical support and advice to ensure that low and middle income countries can implement salt monitoring activities effectively.